وتعيين صفاتها الفسلجية والوظيفيةPeriplaneta americana L.عزل البكتريا الهوائية من الجهاز الهضمي لمصرصر الامريكي - برهان الدين, سناء; الجنابي, سهيلة داوود سلمان; سلمان, شذى (Al-Nahrain Journal of Science, 2012)
Hundred bacterial isolates were obtained from 50 samples of Cockroaches (Periplaneta americana L.). The morphological and physiological characters of the isolates were determined, Results revealed that 34% of the isolates were belonging to Bacillus, 16%, Pseudomonas , Escherichia coli 16% , 14% Serratia, 12% Klebsiella and 8% Enterobacter. All isolates grew at 37˚c, 72% of them had the ability to grow at 45˚c, Pseudomonas isolates only grew at 10˚c. All bacterial isolates favored a medium with pH 7, while 98% and 96% of them were able to grow at pH 5 and 9 but no growth at pH 3.The effect of different concentrations of sucrose and sodium chloride on growth of bacteria was determined. All isolates were able to tolerate 5 and 10% sucrose while 18% of them grew at 7% NaCL but not at 10%.Production of different enzymes from these isolates was examined, it was found that all isolates produce lipase and catalase, 84% produce Coagulase, 76% produce protease,58% produce oxidase, 52% produce amylase and 32% produce urease but no one produce cellulase.